NÃO PERTURBE, ESTAMOS EM SUPERVISÃO: O LUGAR DA SUPERVISÃO NO PROCESSO DE FORMAÇÃO PROFISSIONAL - Soares, Flávia G.; Santos, Pablo P. S. D.; Mohr, Priscila H.; Mai, Luciana V. K.; Melo, Nairana M. d. (Salão do Conhecimento, 2013)
Resumo